Cultural moves : African Americans and the politics of representation - Gray, Herman, 1950- (American crossroads, 2005)
"Examines the importance of culture in the push for black political power and social recognition and argues the key black cultural practices have been notable in reconfiguring the shape and texture of social and cultural life in the U.S. Drawing on examples from jazz, television, and academia, Gray highlights cultural strategies for inclusion in the dominant culture as well as cultural tactics that move beyond the quest for mere recognition by challenging, disrupting, and unsettling dominant cultural representations and institutions. In the end, Gray challenges the conventional wisdom about the centrality of representation and politics in black cultural production"--Provided by publisher